الاقتصاد البنفسجي ،التنوع الثقافي والتنمية المستدامة - جيلالي, امنه (جامعة الوادي - University of Eloued, 2022)
الاقتصاد البنفسجي لون جدد من ألوان الاقتصاد يقوم على إضفاء الطابع الإنساني على العولمة من خلال تثمين البعد الثقافي للسلع والخدمات ،للتوفيق بين التنمية الاقتصادية والاستدامة انه نموذج قائم على التنمية الثقافية للخروج من الأزمات الاقتصادية. يرتبط بالتنوع الثقافي في علاقة تفاعلية تقوم على مبدأ رابح رابح، لان التنوع الثقافي يمثل مستودع المعارف والأفكار الإبداعية التي يقوم عليها الاقتصاد البنفسجي ، و هذا الأخير يعمل على تثمين وحماية التنوع الثقافي في ظل العولمة. The purple economy is a new color of the economy based on the humanization of globalization by assessing the cultural dimension of goods and services, to reconcile economic development and sustainability. It is a model based on cultural development to get out of economic crises. It is linked to cultural diversity in an interactive relationship based on the winwin principle, because cultural diversity represents a reservoir of information and innovative ideas underpinning the purple economy. And this latter works to strengthen and preserve cultural diversity in the light of globalization
Purple economy, cultural diversity and sustainable development: interactive relationships
مقال
Keywords: الاقتصاد البنفسجي ، التنوع الثقافي ، التنمية المستدامة